Diversidade de formigas (Hymenoptera: Formicidae) em plantio de teca no Pantanal Mato-grossense - Santos, Jeane Rodrigues Lopes (2017)
Although teak monoculture is one of the most commercialized and profitable forest species in the state of Mato Grosso, there is still a lack of information on the diversity of ants that occur within these plantations in the state. Therefore, the present study aimed to evaluate the diversity of ants in teak monoculture, using two methods of collection, pitfall traps and Winkler extractor. The samples were collected between May 2015 and May 2016, at Fazenda Campina, in the municipality of Nossa Senhora do Livramento-MT, with a total of 480 samples. The collected individuals were collected and taxonomically identified at the genus and species level, and 13,139 ants were collected in the two sampling methods, with 12,649 individuals collected in the pitffal traps and 356 by the Winkler extractor, belonging to 18 genera and five subfamilies. Myrmicinae, Formicinae were the most representative in quantity of species. The genera Pheidole and Camponotus were representative in number of species. In one year, 28 species were sampled, 26 species of ants collected with pitfall trap and 16 species with Winkler extractor. About 17 species (60.71%) presented an omnivorous food habit, followed by eight species (28.57%) presenting a predatory eating habit, and three (10.71%) being fungus cultivators. In relation to the Shannon index, in the annual period (Winkler extractor) it was the one with the highest diversity index. The species accumulation curve showed that the sampling effort was sufficient.